A method for surface modification of silicon-carbon material for solid-state batteries
Patent Information
- Application Number
- CN202611416942.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-23
AI Technical Summary
[0009]本发明的目的在于提供一种用于固态电池的硅碳材料的表面改性方法,以解决上述背景技术中提出的现有表面改性方法存在的界面兼容性差、机械稳定性不足、完整性与均匀性难以保证以及长循环稳定性不足的问题
1、本发明中,通过设置预处理与活化步骤及原位聚合构建界面相容层,使得硅碳材料表面富含含氧官能团并形成具有良好锂离子传导性的初固化聚合物界面层,从而显著提升改性层与固态电解质之间的化学相容性与界面稳定性,进而降低界面阻抗、抑制副反应发生。
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicon-carbon material surface modification technology, and more specifically, to a method for surface modification of silicon-carbon materials for solid-state batteries. Background Technology
[0002] With the rapid development of electric vehicles, portable electronic devices, and large-scale energy storage systems, high-energy-density and high-safety energy storage technologies have become a research hotspot. Solid-state batteries, which use non-flammable solid electrolytes instead of traditional organic liquid electrolytes, offer higher safety, longer cycle life, and higher energy density potential, and are considered an important direction for the development of next-generation battery technology. A solid-state battery is a lithium-ion battery that uses a solid electrolyte instead of a traditional liquid electrolyte. Its core feature is the conduction of ions through solid materials, while also functioning as a separator. Compared to liquid batteries, it eliminates the flammable electrolyte, significantly improving safety, and is compatible with higher energy density lithium metal anodes, theoretically offering 2-10 times the range of traditional batteries.
[0003] Silicon-carbon composite materials, as anode materials, have become a highly promising choice for high-energy-density anodes due to their high theoretical specific capacity (up to 4200 mAh / g for silicon phase), suitable operating potential, and abundant natural resources. However, silicon materials experience severe volume expansion (>300%) during charge and discharge, leading to particle pulverization, active material shedding, and repeated cracking and reconstruction of the solid electrolyte interface, resulting in rapid capacity decay and decreased cycle performance. In solid-state battery systems, the silicon-carbon anode and solid electrolyte have a solid-solid contact, making the interfacial stress caused by volume expansion even more significant. This easily leads to interface delamination, contact failure, and blockage of ion transport channels, severely restricting the practical application of silicon-carbon materials in solid-state batteries.
[0004] To alleviate the aforementioned problems, existing technologies typically involve surface modification of silicon-carbon materials. Common methods include carbon coating, metal oxide coating, polymer modification, and the construction of core-shell structures. However, in the context of solid-state battery applications, these surface modification methods still suffer from the following prominent problems and drawbacks: Poor interfacial compatibility between modified layers and solid electrolytes: Most surface modified layers (such as non-lithium conductive oxides and inert carbon layers) have insufficient chemical / electrochemical stability with mainstream solid electrolytes such as sulfides and oxides, which are prone to side reactions or the formation of high impedance layers at the interface, resulting in reduced interfacial ion transport efficiency and increased internal resistance of the full cell.
[0005] Insufficient mechanical stability of the modified layer: During repeated volume changes of silicon-carbon materials, the existing modified layer often cracks and peels due to insufficient toughness or weak bonding with the matrix, and cannot continuously maintain the constraint effect on volume expansion, resulting in contact failure between the solid electrolyte and the negative electrode material.
[0006] The integrity and uniformity of the modified layer are difficult to guarantee: especially for nano / micro-scale porous silicon-carbon composite materials, existing coating technologies cannot achieve a completely uniform and dense surface coverage. Local uncovered areas will still be in direct contact with the solid electrolyte, causing side reactions and accelerating performance degradation.
[0007] Insufficient long-cycle stability: Most modification methods only perform well in the initial cycle. As the number of cycles increases, the modified layer structure is gradually destroyed, and the interface side reactions accumulate, leading to a continuous decline in battery capacity, which makes it difficult to meet the long-life requirements of solid-state batteries.
[0008] Therefore, developing a surface modification method for silicon-carbon materials suitable for solid-state batteries, which can enhance interface stability and adapt to silicon-carbon volume changes while maintaining high ionic conductivity, has become a key technological challenge for promoting the industrialization of solid-state batteries. Summary of the Invention
[0009] The purpose of this invention is to provide a surface modification method for silicon-carbon materials used in solid-state batteries, in order to solve the problems of poor interface compatibility, insufficient mechanical stability, difficulty in ensuring integrity and uniformity, and insufficient long-cycle stability of existing surface modification methods mentioned in the background art.
[0010] To achieve the above objectives, the present invention aims to provide a surface modification method for silicon-carbon materials used in solid-state batteries. This method aims to improve the interfacial properties between the silicon-carbon composite material and the solid electrolyte, and includes the following steps: S1. Pretreatment and activation: The silicon-carbon composite anode material is pretreated to obtain surface-activated silicon-carbon material. The pretreatment includes cleaning and surface oxidation treatment. S2. In-situ polymerization to construct an interface compatibility layer: On the surface of the activated silicon-carbon material, an initial-cured polymer interface layer is formed through an in-situ polymerization reaction. S3. Introducing a flexible reinforcement and stress buffer structure: In the middle or on the surface of the polymer interface layer, an elastic reinforcement phase is introduced to construct a stress buffer structure that can adapt to the volume expansion of silicon-carbon materials. S4. Constructing a gradient and densified coating layer: Through a step-by-step coating process, a dense, uniform composite coating layer with a gradient transition to the internal interface layer is constructed outside the stress buffer structure to obtain the coated material. S5. Heat treatment and interface fusion: The coated material is heat-treated in an inert atmosphere or a specific atmosphere to achieve chemical bonding between layers and optimize its interfacial compatibility with the solid electrolyte. S6. Surface functionalization treatment: The heat-treated material is chemically modified to introduce functional groups that can promote lithium-ion conduction or stabilize the solid electrolyte interface film. S7. Post-processing and performance evaluation: The final modified material is cleaned and dried, and its electrochemical performance as a negative electrode for solid-state batteries is evaluated.
[0011] As a further improvement to this technical solution, the specific steps for pretreatment and activation in step S1 are as follows: S11. The silicon-carbon composite anode material is ultrasonically dispersed and cleaned in an organic solvent to remove surface impurities; S12. Place the cleaned silicon-carbon composite anode material in an oxidizing atmosphere or solution for a mild surface oxidation treatment to generate oxygen-containing functional groups. S13. Vacuum dry the oxidized silicon-carbon composite anode material to obtain surface-activated silicon-carbon material.
[0012] As a further improvement to this technical solution, the specific steps for constructing the interface compatibility layer through in-situ aggregation in step S2 are as follows: S21. Preparation of polymerization precursor solution: Dissolve monomer, lithium salt and initiator in an organic solvent at a certain mass ratio to form a homogeneous solution; S22. In-situ polymerization coating: The surface-activated silicon-carbon material obtained in step S1 is uniformly dispersed in the polymerization precursor solution and stirred at a temperature of 40℃-80℃ for 2h-12h, or photopolymerization reaction is carried out under the irradiation of a specific wavelength light source, so that the monomers are polymerized in-situ on the surface of the silicon-carbon material to form a coated polymer gel layer. S23. Washing and Preliminary Curing: After the reaction is completed, the silicon-carbon material coated with the polymer gel layer is separated and washed with a low-boiling-point organic solvent to remove unreacted monomers and free initiators. Then, it is vacuum dried at 40℃-60℃ for 4h-12h to obtain a silicon-carbon composite material with a preliminarily cured polymer interface layer on the surface.
[0013] As a further improvement to this technical solution, in step S21, the monomer is selected from at least one of ethylene oxide, acrylonitrile, and ethylene carbonate, and the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonylimide) and lithium hexafluorophosphate. The mass of the monomer... With the mass of lithium salt The proportions satisfy: The organic solvent is tetrahydrofuran, N-methylpyrrolidone, or acetonitrile, and the total solids content of the polymerization precursor solution is... The total solids content should be controlled between 5% and 20%, with the total solids content determined by the formula. Perform calculations. For the quality of the initiator, This represents the total mass of the polymerization precursor solution.
[0014] As a further improvement to this technical solution, the specific operational steps for introducing the flexible reinforcement and stress buffer structure in step S3 are as follows: S31. Preparation of elastic reinforcing phase precursor: Disperse the elastomer material or crosslinking agent that can crosslink to form an elastic network in an organic solvent to form a uniform dispersion; S32. Constructing a composite buffer structure: The silicon-carbon composite material with a pre-cured polymer interface layer on the surface obtained in step S2 is dispersed in the elastic reinforcing phase precursor. The elastic reinforcing phase precursor is penetrated and loaded into the interior and surface of the pre-cured polymer interface layer by stirring, ultrasonication or impregnation. Then, the elastic reinforcing phase precursor is cured by heating, photocuring or solvent evaporation, and a uniformly distributed elastic reinforcing phase is formed in the pre-cured polymer interface layer, thereby constructing a composite silicon-carbon material with an internal stress buffer network. S33. Post-treatment and stabilization: The composite silicon-carbon material is separated, uncured substances are removed by solvent cleaning, and vacuum dried at 40℃-80℃ for 2h-8h to obtain a structurally stable modified silicon-carbon material with flexible reinforcement and stress buffer structure.
[0015] As a further improvement to this technical solution, the elastomer material is at least one of polyurethane, styrene-butadiene rubber, and polybutadiene, and the crosslinking agent is a multifunctional compound containing double bonds or epoxy groups. The mass of the elastomer material or crosslinking agent... With the quality of monomers The proportions satisfy: .
[0016] As a further improvement to this technical solution, the specific steps for constructing the gradient and densification coating layer in step S4 are as follows: S41. Preparation of gradient coating precursor solutions: Dissolve or disperse the precursor of the coating material, lithium salt and additives in a solvent in proportion to form at least two coating solutions with different concentrations or compositions, wherein the coating material is selected from at least one of polymers, oxides or lithium-containing compounds. S42, Gradient Coating: The modified silicon-carbon material with flexible reinforcement and stress buffer structure obtained in step S33 is sequentially immersed in coating solutions of varying concentrations or different compositions. Coating layers are applied layer by layer by means of immersion, spraying or spin coating. Each layer is pre-cured or dried after coating. S43. Densification treatment: Under an inert atmosphere, the material after layer-by-layer coating is subjected to medium-temperature heat treatment at a temperature of 150℃-350℃ for 2h-8h, so that each coating layer is further fused and forms a dense, uniform composite coating layer with a gradient transition to the internal structure, thus obtaining the coated material.
[0017] As a further improvement to this technical solution, the specific operation steps for heat treatment and interface fusion in step S5 are as follows: S51. Heat treatment atmosphere control: The coated material is placed in a tube furnace or atmosphere furnace and heat-treated in an inert or reducing atmosphere. S52. Stepwise heating treatment: The temperature is continuously increased to 300℃-600℃ at a rate of 1℃ / min-5℃ / min, and held at the target temperature for 2h-10h to promote chemical bonding and interface fusion between layers. S53. Cooling and Collection: The material is continuously cooled to room temperature and collected under a protective atmosphere to obtain the modified silicon-carbon composite material after interfacial fusion.
[0018] As a further improvement to this technical solution, the specific steps for surface functionalization treatment in step S6 are as follows: S61. Preparation of functionalizing reagents: Dissolve compounds containing lithium-ion conducting groups or interface stabilizing groups in an organic solvent to form a functionalizing treatment solution; S62. Surface modification reaction: The heat-treated material is immersed in the functionalized treatment liquid and stirred at a temperature of 20℃-80℃ for 1h-6h to allow functional groups to be chemically grafted or physically adsorbed onto the surface of the material. S63. Cleaning and drying: After the reaction is complete, the material is separated and cleaned with an organic solvent, and then vacuum dried at 40℃-80℃ for 2h-6h to obtain surface-functionalized silicon-carbon modified material.
[0019] As a further improvement to this technical solution, the specific steps for post-processing and performance evaluation in step S7 are as follows: S71. Cleaning and drying: Clean the surface-functionalized material with an organic solvent with a boiling point below 100℃ to remove residual reagents, and then vacuum dry it at a temperature of 60℃-100℃ for 4h-12h. S72. Material Characterization: Characterize the morphology, structure, and composition of the final modified material; S73. Electrochemical performance testing: The modified material is used as the negative electrode active material and assembled with a solid electrolyte and a positive electrode to form a solid battery. Its cycle performance, rate performance and interfacial impedance are tested to evaluate its electrochemical performance as a negative electrode of a solid battery.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In this invention, by setting pretreatment and activation steps and constructing an interface compatibility layer through in-situ polymerization, the surface of silicon-carbon material is rich in oxygen-containing functional groups and forms a pre-cured polymer interface layer with good lithium-ion conductivity, thereby significantly improving the chemical compatibility and interface stability between the modified layer and the solid electrolyte, thereby reducing interface impedance and suppressing the occurrence of side reactions.
[0021] 2. In this invention, by introducing a flexible reinforcement and stress buffer structure, the elastic reinforcement phase is uniformly distributed in the polymer interface layer, thereby effectively absorbing and buffering the volume expansion stress of silicon-carbon materials during charging and discharging, thus preventing the coating layer from cracking and peeling, and maintaining a long-lasting and close contact between the negative electrode and the solid electrolyte.
[0022] 3. In this invention, by constructing a gradient and densified coating layer, the coating layer exhibits a continuous transition in composition and structure from the inside to the outside, thereby achieving complete, uniform and dense coverage of the coating layer, thus avoiding direct contact between the uncovered areas and the electrolyte, and improving the consistency of the interface and long-term electrochemical stability.
[0023] 4. In this invention, through heat treatment, interface fusion and surface functionalization, chemical bonds are formed between the layers and functional groups that promote lithium-ion conduction or stabilize the interface are introduced, thereby strengthening the interlayer bonding force, optimizing the ion transport path, and thus improving the rate performance and cycle life of the full battery. Attached Figure Description
[0024] Figure 1 This is a schematic flowchart of the surface modification method for silicon-carbon materials used in solid-state batteries according to the present invention. Detailed Implementation
[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] like Figure 1 As shown, this invention provides a surface modification method for silicon-carbon materials used in solid-state batteries. This method aims to improve the interfacial properties between the silicon-carbon composite material and the solid electrolyte, and includes the following steps: Step 1: Pretreatment and Activation: The silicon-carbon composite anode material is pretreated to obtain surface-activated silicon-carbon material. The pretreatment includes cleaning and surface oxidation. Specifically: The silicon-carbon composite anode material was ultrasonically dispersed and cleaned in an organic solvent to remove surface impurities. The cleaned silicon-carbon composite anode material is placed in an oxidizing atmosphere or solution for a mild surface oxidation treatment to generate oxygen-containing functional groups. The oxidized silicon-carbon composite anode material was vacuum dried to obtain a surface-activated silicon-carbon material.
[0027] Step 2: In-situ polymerization to construct an interface compatibility layer: On the surface of the activated silicon-carbon material, an initial-cured polymer interface layer is formed through an in-situ polymerization reaction. Specifically: Preparation of polymerization precursor solution: The monomer, lithium salt, and initiator are dissolved in an organic solvent at a certain mass ratio to form a homogeneous solution. The monomer is selected from at least one of ethylene oxide, acrylonitrile, and ethylene carbonate, and the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide and lithium hexafluorophosphate. The mass ratio of the monomer is... With the mass of lithium salt The proportions satisfy: The organic solvent is tetrahydrofuran, N-methylpyrrolidone, or acetonitrile, and the total solids content of the polymerization precursor solution is... The total solids content should be controlled between 5% and 20%, with the total solids content determined by the formula. Perform calculations. For the quality of the initiator, This represents the total mass of the polymerization precursor solution; In-situ polymerization coating: The surface-activated silicon-carbon material obtained in the above steps is uniformly dispersed in the polymerization precursor solution, and stirred at a temperature of 40℃-80℃ for 2h-12h, or photopolymerization is carried out under the irradiation of a specific wavelength light source, so that the monomers are polymerized in-situ on the surface of the silicon-carbon material to form a coated polymer gel layer. Washing and initial curing: After the reaction is completed, the silicon-carbon material coated with the polymer gel layer is separated and washed with a low-boiling-point organic solvent to remove unreacted monomers and free initiators. Then, it is vacuum dried at 40℃-60℃ for 4h-12h to obtain a silicon-carbon composite material with an initial cured polymer interface layer on the surface.
[0028] Step 3: Introducing a flexible reinforcement and stress buffer structure: An elastic reinforcing phase is introduced into the middle or surface of the polymer interface layer to construct a stress buffer structure that can adapt to the volume expansion of the silicon-carbon material. Specifically: Preparation of the elastic reinforcing phase precursor: An elastomer material or a crosslinking agent capable of forming an elastic network is dispersed in an organic solvent to form a uniform dispersion. The elastomer material is at least one of polyurethane, styrene-butadiene rubber, and polybutadiene. The crosslinking agent is a multifunctional compound containing double bonds or epoxy groups. The mass of the elastomer material or crosslinking agent... With the quality of monomers The proportions satisfy: ; Constructing a composite buffer structure: The silicon-carbon composite material with a pre-cured polymer interface layer on the surface obtained in the above steps is dispersed in the elastic reinforcing phase precursor. The elastic reinforcing phase precursor is penetrated and loaded into the interior and surface of the pre-cured polymer interface layer by stirring, ultrasonication or impregnation. Then, the elastic reinforcing phase precursor is cured by heating, photocuring or solvent evaporation, forming a uniformly distributed elastic reinforcing phase in the pre-cured polymer interface layer, thereby constructing a composite silicon-carbon material with an internal stress buffer network. Post-treatment and stabilization: The composite silicon-carbon material is separated, uncured substances are removed by solvent cleaning, and vacuum dried at 40℃-80℃ for 2h-8h to obtain a structurally stable modified silicon-carbon material with flexible reinforcement and stress buffer structure.
[0029] Step 4: Constructing a Gradient and Dense Coating Layer: Through a step-by-step coating process, a dense, uniform composite coating layer with a gradient transition to the internal interface layer is constructed outside the stress buffer structure to obtain the coated material. Specifically: Preparation of gradient coating precursor solutions: Dissolve or disperse the precursor of the coating material, lithium salt and additives in a solvent in proportion to form at least two coating solutions with different concentrations or compositions, wherein the coating material is selected from at least one of polymers, oxides or lithium-containing compounds; Gradient coating layer by layer: The modified silicon-carbon material with flexible reinforcement and stress buffer structure obtained in the above steps is sequentially immersed in coating solutions of varying concentrations or different compositions. Coating layers are applied layer by layer by means of immersion, spraying or spin coating. Each coating layer is pre-cured or dried after coating. Densification treatment: Under an inert atmosphere, the material after layer-by-layer coating is subjected to medium-temperature heat treatment at a temperature of 150℃-350℃ for 2h-8h, so that the coating layers are further fused and form a dense, uniform composite coating layer with a gradient transition to the internal structure, thus obtaining the coated material.
[0030] Step 5: Heat Treatment and Interface Integration: The coated material is heat-treated under an inert atmosphere or a specific atmosphere to achieve chemical bonding between the layers and optimize its interfacial compatibility with the solid electrolyte. Specifically: Heat treatment atmosphere control: The coated material is placed in a tube furnace or atmosphere furnace and heat-treated in an inert or reducing atmosphere. Stepwise heating treatment: The temperature is continuously increased to 300℃-600℃ at a rate of 1℃ / min-5℃ / min, and held at the target temperature for 2h-10h to promote chemical bonding and interfacial fusion between layers. Cooling and collection: The material was continuously cooled to room temperature and collected under a protective atmosphere to obtain the modified silicon-carbon composite material after interfacial fusion.
[0031] Step 6: Surface Functionalization Treatment: The heat-treated material undergoes surface chemical modification to introduce functional groups that can promote lithium-ion conduction or stabilize the solid electrolyte interface film. Specifically: Preparation of functionalized reagents: Dissolve compounds containing lithium-ion conducting groups or interfacial stabilizing groups in an organic solvent to form a functionalized treatment solution; Surface modification reaction: The heat-treated material is immersed in the functionalized treatment liquid and stirred at 20℃-80℃ for 1h-6h to allow functional groups to be chemically grafted or physically adsorbed onto the surface of the material. Cleaning and drying: After the reaction, the material was separated and cleaned with an organic solvent, and then vacuum dried at 40℃-80℃ for 2h-6h to obtain surface-functionalized silicon-carbon modified material.
[0032] Step 7: Post-processing and Performance Evaluation: The final modified material is cleaned and dried, and its electrochemical performance as a solid-state battery anode is evaluated. Specifically: Cleaning and drying: The surface-functionalized material is cleaned with an organic solvent with a boiling point below 100℃ to remove residual reagents, and then vacuum dried at a temperature of 60℃-100℃ for 4h-12h. Material characterization: The morphology, structure, and composition of the final modified material were characterized. Electrochemical performance testing: The modified material is used as the negative electrode active material and assembled with a solid electrolyte and a positive electrode to form a solid-state battery. Its cycle performance, rate performance and interfacial impedance are tested to evaluate its electrochemical performance as a negative electrode of a solid-state battery.
[0033] Example 1
[0034] In one specific embodiment, the present invention provides a surface modification method for silicon-carbon materials used in solid-state batteries, which specifically includes the following steps: Step 1, Pretreatment and Activation: Commercial nano-silicon-carbon composite material (Si / C, silicon content approximately 30 wt%, average particle size approximately 200 nm) was used as the starting material. It was placed in anhydrous ethanol and ultrasonically dispersed for 1 hour at 300 W. After centrifugation, it was washed three times with deionized water. Next, the washed material was immersed in a 5% (w / w) hydrogen peroxide aqueous solution and gently oxidized at 50°C for 4 hours to generate abundant oxygen-containing functional groups such as -OH and -COOH on the material surface. After oxidation, it was washed with deionized water until neutral, and then dried in a vacuum drying oven at 80°C for 12 hours to obtain surface-activated silicon-carbon material.
[0035] Step 2: In-situ aggregation to build the interface compatibility layer: Preparation of polymerization precursor solution: Ethylene oxide monomer, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and azobisisobutyronitrile (AIBN) were added to tetrahydrofuran at a mass ratio of 100:15:1 and stirred until completely dissolved to obtain a homogeneous solution with a total solid content of 10%.
[0036] The surface-activated silicon-carbon material obtained in the above steps is dispersed in the above polymerization precursor solution at a solid-liquid ratio of 1:20. The mixture is mechanically stirred at 60°C for 8 hours to allow ethylene oxide to undergo in-situ ring-opening polymerization on the surface of the silicon-carbon particles, forming a polyethylene oxide gel coating layer with a thickness of about 30-50 nm.
[0037] After the reaction was completed, the coating material was separated by centrifugation and washed three times with acetone with a boiling point below 80°C to remove unreacted monomers and residual initiators. Then, it was vacuum dried at 50°C for 8 hours to obtain a silicon-carbon composite material with a pre-cured polymer interface layer on the surface.
[0038] Step 3: Introduce flexible reinforcement and stress buffer structures: Preparation of elastic reinforcing phase precursor: Polyurethane elastomer microspheres (average particle size of about 100 nm) were dispersed in N-methylpyrrolidone to prepare a uniform dispersion with a mass fraction of 8%.
[0039] The silicon-carbon composite material coated with the pre-cured polymer interface layer obtained in the above steps was added to the above dispersion and ultrasonically treated for 30 minutes to fully impregnate it. Then, it was stirred and reacted at 70°C for 4 hours to allow the polyurethane microspheres to be embedded and crosslinked in the PEO matrix to form an interpenetrating network structure.
[0040] After the reaction was completed, the material was centrifuged, washed with ethanol to remove uncured material, and then vacuum dried at 60°C for 6 hours to obtain a modified silicon-carbon material with an internal stress buffer network.
[0041] Step 4: Constructing a gradient and densification coating layer: Preparation of gradient coating solutions: First layer: Dissolve lithium acetate and aluminum isopropoxide in ethanol at a lithium-aluminum molar ratio of 1:1 to prepare a solution with a concentration of 0.1 mol / L; Second layer: Dissolve sucrose in deionized water to prepare a 15% solution.
[0042] The material obtained in the above steps is first immersed in the first layer solution, soaked for 10 minutes, and then taken out and pre-fired at 120°C for 1 hour to form an amorphous lithium aluminum oxide transition layer; then it is immersed in the second layer solution, soaked for 5 minutes, and then taken out and heat-treated at 180°C for 2 hours to solidify the carbonization precursor.
[0043] The above-mentioned coating material was placed in a tube furnace and heated to 600°C at 5°C / min under argon protection. The temperature was maintained for 2 hours to carbonize the sucrose and form a dense amorphous carbon layer, ultimately obtaining a silicon-carbon material with a gradient composite coating layer.
[0044] Step 5: Heat treatment and interface integration: The coated material from the above steps was placed in a tube furnace with a hydrogen / argon mixed atmosphere (5% H2 volume fraction) and heated to 450°C at a rate of 2°C / min, held at that temperature for 4 hours, and then allowed to cool naturally to room temperature. This process promotes chemical bonding between PEO segments, the lithium aluminum oxide layer, and the amorphous carbon layer, enhancing interlayer bonding and interfacial fusion.
[0045] Step 6: Surface functionalization treatment: Preparation of functionalized treatment solution: Dissolve lithium fluoride and lithium dihydrogen phosphate in anhydrous ethanol at a mass ratio of 1:1 to prepare a solution with a total concentration of 0.05 mol / L.
[0046] The heat-treated material from step five was immersed in the aforementioned functionalizing solution and stirred at 40°C for 5 hours to allow Li to be chemically adsorbed onto the material surface. + and PO4 3- After the reaction, the mixture was centrifuged, washed three times with ethanol, and vacuum dried at 70°C for 4 hours to obtain a silicon-carbon modified material with lithium-ion conductive and interface-stabilizing functional groups on its surface.
[0047] Step 7: Post-processing and performance evaluation: The final modified material obtained in S6 was washed three times with ethanol with a boiling point below 100°C to remove residual reagents, and then vacuum dried at 90°C for 10 hours.
[0048] The modified material was characterized by scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and X-ray diffraction to confirm its surface morphology, coating structure, and chemical composition.
[0049] The modified material was used as the negative electrode active material and assembled into an all-solid-state coin cell with a Li6PS5Cl sulfide solid electrolyte and an NCM811 positive electrode. Electrochemical performance was tested at 25°C. The results showed that the modified silicon-carbon negative electrode achieved an initial discharge specific capacity of 1850 mAh / g at 0.1C rate and an initial coulombic efficiency of 91.2%. After 800 cycles at 1C rate, the capacity retention was still as high as 87.5%, and the interfacial impedance was reduced by approximately 65% compared to the unmodified material.
[0050] Example 2 In another embodiment, the monomer in the second step was changed to acrylonitrile, the lithium salt to lithium hexafluorophosphate, the elastic reinforcing phase in the third step was styrene-butadiene rubber latex, and the lithium oxide and aluminum oxide composite layer was deposited layer by layer using atomic layer deposition technology in the fourth step. The remaining steps were similar to those in Example 1. The resulting modified silicon-carbon anode retained 84.3% of its capacity after 1000 cycles at 0.5C, demonstrating excellent long-term cycling stability and interface compatibility.
[0051] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for surface modification of silicon-carbon materials for solid-state batteries, characterized in that, This method aims to improve the interfacial properties between silicon-carbon composite materials and solid electrolytes, and includes the following steps: S1. Pretreatment and activation: The silicon-carbon composite anode material is pretreated to obtain surface-activated silicon-carbon material. The pretreatment includes cleaning and surface oxidation treatment. S2. In-situ polymerization to construct an interface compatibility layer: On the surface of the activated silicon-carbon material, an initial-cured polymer interface layer is formed through an in-situ polymerization reaction. S3. Introducing a flexible reinforcement and stress buffer structure: In the middle or on the surface of the polymer interface layer, an elastic reinforcement phase is introduced to construct a stress buffer structure that can adapt to the volume expansion of silicon-carbon materials. S4. Constructing a gradient and densified coating layer: Through a step-by-step coating process, a dense, uniform composite coating layer with a gradient transition to the internal interface layer is constructed outside the stress buffer structure to obtain the coated material. S5. Heat treatment and interface fusion: The coated material is heat-treated in an inert atmosphere or a specific atmosphere to achieve chemical bonding between layers and optimize its interfacial compatibility with the solid electrolyte. S6. Surface functionalization treatment: The heat-treated material is chemically modified to introduce functional groups that can promote lithium-ion conduction or stabilize the solid electrolyte interface film. S7. Post-processing and performance evaluation: The final modified material is cleaned and dried, and its electrochemical performance as a negative electrode for solid-state batteries is evaluated.
2. The surface modification method for silicon-carbon materials used in solid-state batteries according to claim 1, characterized in that, The specific steps for pretreatment and activation in step S1 are as follows: S11. The silicon-carbon composite anode material is ultrasonically dispersed and cleaned in an organic solvent to remove surface impurities; S12. Place the cleaned silicon-carbon composite anode material in an oxidizing atmosphere or solution for a mild surface oxidation treatment to generate oxygen-containing functional groups. S13. Vacuum dry the oxidized silicon-carbon composite anode material to obtain surface-activated silicon-carbon material.
3. The surface modification method for silicon-carbon materials used in solid-state batteries according to claim 1, characterized in that, The specific steps for constructing the interface compatibility layer through in-situ aggregation in step S2 are as follows: S21. Preparation of polymerization precursor solution: Dissolve monomer, lithium salt and initiator in an organic solvent at a certain mass ratio to form a homogeneous solution; S22. In-situ polymerization coating: The surface-activated silicon-carbon material obtained in step S1 is uniformly dispersed in the polymerization precursor solution and stirred at a temperature of 40℃-80℃ for 2h-12h, or photopolymerization reaction is carried out under the irradiation of a specific wavelength light source, so that the monomers are polymerized in-situ on the surface of the silicon-carbon material to form a coated polymer gel layer. S23. Washing and Preliminary Curing: After the reaction is completed, the silicon-carbon material coated with the polymer gel layer is separated and washed with a low-boiling-point organic solvent to remove unreacted monomers and free initiators. Then, it is vacuum dried at 40℃-60℃ for 4h-12h to obtain a silicon-carbon composite material with a preliminarily cured polymer interface layer on the surface.
4. The surface modification method for silicon-carbon materials used in solid-state batteries according to claim 3, characterized in that, In step S21, the monomer is selected from at least one of ethylene oxide, acrylonitrile, and ethylene carbonate; the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonylimide) and lithium hexafluorophosphate; and the mass of the monomer is... With the mass of lithium salt The proportions satisfy: The organic solvent is tetrahydrofuran, N-methylpyrrolidone, or acetonitrile, and the total solids content of the polymerization precursor solution is... The total solids content should be controlled between 5% and 20%, with the total solids content determined by the formula. Perform calculations. For the quality of the initiator, This represents the total mass of the polymerization precursor solution.
5. The surface modification method for silicon-carbon materials used in solid-state batteries according to claim 4, characterized in that, The specific steps for introducing the flexible reinforcement and stress buffer structure in step S3 are as follows: S31. Preparation of elastic reinforcing phase precursor: Disperse the elastomer material or crosslinking agent that can crosslink to form an elastic network in an organic solvent to form a uniform dispersion; S32. Constructing a composite buffer structure: The silicon-carbon composite material with a pre-cured polymer interface layer on the surface obtained in step S2 is dispersed in the elastic reinforcing phase precursor. The elastic reinforcing phase precursor is penetrated and loaded into the interior and surface of the pre-cured polymer interface layer by stirring, ultrasonication or impregnation. Then, the elastic reinforcing phase precursor is cured by heating, photocuring or solvent evaporation, and a uniformly distributed elastic reinforcing phase is formed in the pre-cured polymer interface layer, thereby constructing a composite silicon-carbon material with an internal stress buffer network. S33. Post-treatment and stabilization: The composite silicon-carbon material is separated, uncured substances are removed by solvent cleaning, and vacuum dried at 40℃-80℃ for 2h-8h to obtain a structurally stable modified silicon-carbon material with flexible reinforcement and stress buffer structure.
6. The surface modification method for silicon-carbon materials used in solid-state batteries according to claim 5, characterized in that, The elastomer material is at least one of polyurethane, styrene-butadiene rubber, and polybutadiene; the crosslinking agent is a multifunctional compound containing double bonds or epoxy groups; and the mass of the elastomer material or crosslinking agent is specified. With the quality of monomers The proportions satisfy: .
7. The surface modification method for silicon-carbon materials used in solid-state batteries according to claim 5, characterized in that, The specific steps for constructing the gradient and densification coating layer in step S4 are as follows: S41. Preparation of gradient coating precursor solutions: Dissolve or disperse the precursor of the coating material, lithium salt and additives in a solvent in proportion to form at least two coating solutions with different concentrations or compositions, wherein the coating material is selected from at least one of polymers, oxides or lithium-containing compounds. S42, Gradient Coating: The modified silicon-carbon material with flexible reinforcement and stress buffer structure obtained in step S33 is sequentially immersed in coating solutions of varying concentrations or different compositions. Coating layers are applied layer by layer by means of immersion, spraying or spin coating. Each layer is pre-cured or dried after coating. S43. Densification treatment: Under an inert atmosphere, the material after layer-by-layer coating is subjected to medium-temperature heat treatment at a temperature of 150℃-350℃ for 2h-8h, so that each coating layer is further fused and forms a dense, uniform composite coating layer with a gradient transition to the internal structure, thus obtaining the coated material.
8. The surface modification method for silicon-carbon materials used in solid-state batteries according to claim 7, characterized in that, The specific steps for heat treatment and interface fusion in step S5 are as follows: S51. Heat treatment atmosphere control: The coated material is placed in a tube furnace or atmosphere furnace and heat-treated in an inert or reducing atmosphere. S52. Stepwise heating treatment: The temperature is continuously increased to 300℃-600℃ at a rate of 1℃ / min-5℃ / min, and held at the target temperature for 2h-10h to promote chemical bonding and interface fusion between layers. S53. Cooling and Collection: The material is continuously cooled to room temperature and collected under a protective atmosphere to obtain the modified silicon-carbon composite material after interfacial fusion.
9. The surface modification method for silicon-carbon materials used in solid-state batteries according to claim 8, characterized in that, The specific steps for surface functionalization in step S6 are as follows: S61. Preparation of functionalizing reagents: Dissolve compounds containing lithium-ion conducting groups or interface stabilizing groups in an organic solvent to form a functionalizing treatment solution; S62. Surface modification reaction: The heat-treated material is immersed in the functionalized treatment liquid and stirred at a temperature of 20℃-80℃ for 1h-6h to allow functional groups to be chemically grafted or physically adsorbed onto the surface of the material. S63. Cleaning and drying: After the reaction is complete, the material is separated and cleaned with an organic solvent, and then vacuum dried at 40℃-80℃ for 2h-6h to obtain surface-functionalized silicon-carbon modified material.
10. The surface modification method for silicon-carbon materials used in solid-state batteries according to claim 1, characterized in that, The specific steps for post-processing and performance evaluation in step S7 are as follows: S71. Cleaning and drying: Clean the surface-functionalized material with an organic solvent with a boiling point below 100℃ to remove residual reagents, and then vacuum dry it at a temperature of 60℃-100℃ for 4h-12h. S72. Material Characterization: Characterize the morphology, structure, and composition of the final modified material; S73. Electrochemical performance testing: The modified material is used as the negative electrode active material and assembled with a solid electrolyte and a positive electrode to form a solid battery. Its cycle performance, rate performance and interfacial impedance are tested to evaluate its electrochemical performance as a negative electrode of a solid battery.